Happy Together or Happy Alone? The Tension between the Market and the Family in the Context of Culture - Michalski, Michał A. (Journal of Applied Cultural Studies, 2015)
The article explores the interactions between the family and the market in the context of the happiness and tensions that exist between these two social institutions. The analysis undertaken here also stresses the importance of culture, understood as the norms, values and beliefs which are important for a wide range of actions and processes within a society, and treats it as a useful perspective for the explanation of complex socio economic phenomena. Firstly, the nature and mutual dependence of these two spheres is characterized in order to highlight that the desired social order cannot function without any of them. In this respect the article also aims to explain the role that the family plays in society and the happiness achieved by its members. At the same time, it is stressed that the proper functioning of society depends largely on the vision of a man that a given society accepts. By doing this, the limitations of the anthropological assumptions of the dominant neoclassical economics are indicated and discussed. Secondly, the article shows how the family dimension of human life – social in its nature – is intrinsically connected with the issue of happiness. It is important to stress this because to a large extent happiness in economics and different happiness indices seem to limit their analyses to subjective individual well-being. Finally, the article states that although market and family are to an extent complementary, the proper socio-cultural hierarchy and policies based on it should stress the priority of the latter. Evidence of different kinds for such a standpoint is subsequently presented. In the end, the categories of ‘social’ and ‘human’ capital and their correlation is engaged to improve understanding of the fact that a well-functioning family is a necessary condition for the development and long-term flourishing of the market.